Gracilis muscle flap combined with a laparoscopic transabdominal approach is effective in the treatment of post-prostatectomy rectourethral fistula: A case report. (March 2022) - Takeda, Tomohiro; Shonaka, Tatsuya; Tani, Chikayoshi; Hayashi, Toshihiko; Kakizaki, Hidehiro; Sumi, Yasuo
Abstract: Introduction: Rectourethral fistula (RUF) after prostatectomy is a rare complication; however, when it occurs it is likely to be intractable and treatment requires surgical closure of the fistula. Several approaches to fistula closure have been reported, but there is no established treatment. Case presentation: The patient was a 66-year-old man who had undergone robot-assisted laparoscopic radical prostatectomy for prostate cancer. On the 16th postoperative day, RUF was diagnosed. Cystostomy, laparoscopic ileostomy and transanal fistula closure were performed, and conservative treatment was continued for 5 months; however, the RUF remained, so the patient underwent fistula closure with a gracilis muscle flap using both transperineal and laparoscopic manipulation. Because it was a high fistula, the RUF was difficult to fill with a transperineal approach alone; however, in combination with laparoscopic manipulation, the appropriate filling of the fistula was possible. Clinical discussion: Although few reports have described the use of the laparoscopic transabdominal approach in combination with a transperineal gracilis muscle flap, the advantages of this technique are that the superior part of the fistula can be dissected, the flap can be filled more securely than with a transperineal approach alone, and transabdominal manipulation can be performed in a less invasive manner. In addition, by coordinating perineal and laparoscopic manipulation, we were able to close the fistula without organ damage by safe dissection. Conclusion: The laparoscopic approach is useful for RUF closure because it allows the interposition of the flap to reliably fill the space between the bladder and the rectum. Highlights: The rectourethral fistula is a rare complication of total prostatectomy, but when it becomes intractable, it is difficult to treat. Surgical treatment is required, but there is no standard technique. We used a laparoscopic approach in combination with gracilis muscle flap filling via a transperineal approach. To our knowledge, this technique has only been reported in only one other case in the Japanese literature. In a case of high rectourethral fistula, the gracilis muscle flap with a laparoscopic approach allowed for safe and secure flap filling.